OSTEOARTICULAR COMPLICATIONS OF BRUCELLOSIS - Erdal Gilgil; Bülent Bütün (Archives of Rheumatology, 2002)
Brucellosis is a widely spread zoonosis in Turkey, as is in the Middle East. It may lead to protean and severe osteoarticular complications, so it seems essential to identify the clinical features of osteoarticular brucellosis to reach a clear diagnosis. Forty-three cases of osteoarticular brucellosis were included in this study. All of the patients underwent direct radiography and radionuclide bone scanning. CT and/or MRI of the involved area were performed if needed. Of 43 patients, 26 were females and 17 were males; mean age was 45,2 ± 15,2 years. The osteoarticular complications were classified as: spondylitis in 25 patients, sacroiliitis in 10 patients, peripheral arthritis in 21 patients, osteomyelitis in 1 patient, bursitis in 1 patient and tendinitis in 1 patient. The peripheral joint involvement was usually of mono- or oligoarticular pattern. The most commonly affected peripheral joints were hips and knees, respectively. In the endemic areas, brucellosis must be taken into consideration in the patients with rheumatic manifestations, especially in those with inflammatory low back pain and/or mono-oligoarthritis.